Determinan Kepatuhan Minum Obat Pasien Tuberkulosis Paru - Christine Vita Gloria; Zulmeliza Rasyid; Sherly Vermita W; Elmia Kursani; Bizanti Umayyah (Jurnal Kesmas Asclepius, 2019)
This study aims to see whether the determinants are related to treatment compliance for pulmonary tuberculosis patients at the 2019 health center. This type of research is a quantitative observational cross-sectional design. The results showed that with a P value of 0.05, there was a significant relationship between knowledge (P value = 0.005 and POR = 14.276), attitudes (P value = 0.506 and POR = 1.615), family support (P value = 0.038 and POR = 1,961), the role of health workers (P values = 0.026 and POR = 4.440), with medication adherence for pulmonary tuberculosis patients. Conclusions, of the 4 variables there are 3 variables related to adherence to taking pulmonary TB drugs in the Work Area of the Siak Hulu II Health Center, namely knowledge, family support, and the role of health workers and 1 unrelated variable, attitude. Keywords: Obedience, Medicine, Lung Tuberculosis